Translanguaging dan Dampaknya Terhadap Pembelajaran Makna Kata (Frasa) Bahasa Arab pada Kelas PKPBA UIN Malang - Muhammad Fahrudin Nur; Rahmania Auriel Zaeni; M Sholih Salimul Uqba (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
The purpose of this study is to analyze the phenomenon of translanguaging and its impact in the context of education, especially in teaching Arabic as a foreign language in the Special Program for Arabic Language Development (PKPBA) UIN Maulana Malik Ibrahim Malang. The methods used are literature study and observation to observe translanguaging (Indonesian, local language, and Arabic) that occurs in PKPBA. The results of the literature study revealed that translanguaging affects the performance of students with multilingual backgrounds (Indonesian, local languages, and Arabic). The result of the discussion in this article is that translanguaging always occurs in learning Arabic as a foreign language. Translanguaging is considered effective in learning at PKPBA, this is because translaguaging can increase student participation and activeness in learning. Recommendations for improvement include the development of multilingual learning materials, training for teachers, recognition of students' language diversity, further research on the impact of translanguaging, and the development of a more inclusive curriculum.